MEMBANGUN KEMAMPUAN ESTIMASI SISWA SEKOLAH DASAR MELALUI PENDEKATAN MATEMATIKA REALISTIK INDONESIA (PMRI) - wawan wawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
The purpose of this study was to describe the learning process using PMRI approach as a solution to build the capacity estimation at the elementary school, this research is to find out the obstacles of the implementation of PMRI approach in the classroom and to know the results of the application of PMRI approach with regard to the ability of elementary students estimate. The approach used in this study is a qualitative approach. The type of research is a class action (PTK). The subjects were students of class V SD N I Sokomoyo with 28 students. Learning core activities include: delivery relistik issues relating to the problems of estimation, group discussions, presentations and conclusions. The results showed that the application of PMRI can foster activeness, courage in presenting their opinions and be able to grow and improve estimates of elementary school students. As for the obstacles that arise in the application of PMRI in class include: a) Students tend to be rowdy in class the more so when the division of the group, and b) Students are afraid to present the results of group discussion in class Keywords: PMRI, estimation, realistic